RNF180 Inhibits Proliferation and Promotes Apoptosis of Colorectal Cancer Through Ubiquitination of WISP1 - Wei, Feng; Ba, Sang; Jin, Mei; Ci, Ren; Wang, Xuelian; E, Fusheng; Long, Ziwen (Frontiers in Cell and Developmental Biology, 2021)
Colorectal cancer (CRC) is the third leading cause of cancer-related deaths globally and is biologically and clinically heterogeneous. Due to lack of gene expression signatures for risk and prognosis stratification of CRC, identifying novel molecular biomarkers and therapeutic targets may potentially improve CRC prognosis and treatment. RNF180 has been shown to play key contributions to the development of several types of cancers. In the current study, we investigate its role in CRC. In this study, we show that RNF180 expression was significantly downregulated in human CRC tumors and cell lines. Overexpression of RNF180 in CRC cells markedly inhibited cell viability and induced cell apoptosis, while depletion of RNF180 dramatically enhanced cell survival. Moreover, WISP1 was found to be the critical downstream molecule that mediated the tumor suppressive effects of RNF180. Mechanistically, RNF180 ubiquitinated WISP1, resulting in WISP1 downregulation and ultimately leading to suppression of CRC tumor growth in patient-derived xenograft (PDX) mouse models. Last, 5-FU and RNF180 had synergetic effect on the apoptosis induction and tumor growth inhibition. Our findings revealed a crucial role of RNF180 in suppressing tumor growth by ubiquitinating WISP1 in CRC. Moreover, RNF180 strongly influenced chemosensitivity of CRC cells.